2021
DOI: 10.1016/j.jad.2021.08.083
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and neurophysiological differences in working memory function of depressed patients and healthy controls

Abstract: Objective: Major depressive disorder (MDD) is associated with deficits in working memory.Several cognitive subprocesses interact to produce working memory, including attention, encoding, maintenenace and manipulation. We sought to clarify the contribution of functional deficits in these subprocesses in MDD by varying cognitive load during a working memory task.Methods: 41 depressed participants and 41 age-and gender-matched healthy controls performed the n-back working memory task at three levels of difficulty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 124 publications
2
7
2
Order By: Relevance
“…We also found that depressive symptoms were significantly negatively correlated with the correct rate of completion of the working memory task, but not with the response time of completing the working memory task, which is inconsistent with the results of previous studies[ 17 , 48 ], which may be due to the difference in task paradigms, as previous studies of working memory used both the 1-back and 2-back working memory tasks, whereas the present study used only the 2-back task. This result may be due to the difference in task paradigms, as the 1-back task is simpler for college students, and a “ceiling effect” may occur[ 49 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We also found that depressive symptoms were significantly negatively correlated with the correct rate of completion of the working memory task, but not with the response time of completing the working memory task, which is inconsistent with the results of previous studies[ 17 , 48 ], which may be due to the difference in task paradigms, as previous studies of working memory used both the 1-back and 2-back working memory tasks, whereas the present study used only the 2-back task. This result may be due to the difference in task paradigms, as the 1-back task is simpler for college students, and a “ceiling effect” may occur[ 49 ].…”
Section: Discussioncontrasting
confidence: 99%
“…, pleasure deficit) are highly correlated with impairment of working memory[ 8 , 10 - 12 ]. Related brain imaging studies have found that depressed individuals show greater activation in the cingulate cortex and prefrontal lobe when completing N -back tasks compared to healthy individuals[ 13 - 17 ], suggesting that to achieve the same level of performance on working memory tasks as healthy individuals, depressed individuals need to mobilize more cognitive resources and exert greater cognitive effort. Comparisons were made between depressed and non-depressed college students on a working memory task, and it was found that the correct rate of depressed subjects was lower than that of healthy subjects, and the reaction time was higher than that of healthy subjects, both of which were statistically significant[ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found 38 studies that presented results for a concomitant occurrence of P300 and alpha power (or amplitude). In 17 studies using EEG, results indicated an overlap in cortical regions of P300 and alpha amplitude decrease, as well as a similar time windows of their occurrence (Peng et al, 2012, Chen et al, 2013, Dong et al, 2015, Shou et al, 2015, Tang et al, 2015, Wu et al, 2015, Fabi et al, 2017, López-Caneda et al, 2017, Vilà-Balló et al, 2017, Fabi et al, 2018, Michelini et al, 2018, Román-López et al, 2019, Kao et al, 2020, Yu et al, 2020, Zhang et al, 2020, Nikolin et al, 2021, Paolicelli et al, 2021). Similar observations were made using MEG (Ishii et al, 2009).…”
Section: Introductionmentioning
confidence: 86%
“…MDD is associated with deficits in WM. Individuals with depression dedicate a higher level of cognitive processing and more cognitive resources to achieve WM performance comparable with that of healthy individuals (Nikolin, Tan, Martin, et al, 2021). Furthermore, it is difficult for individuals with depression to inhibit and update negative information in WM (Joormann et al, 2011).…”
Section: The Function Of the Ce In Depressive Disordersmentioning
confidence: 99%